Tom Angier’s Natural Law vs. the Natural Law Formula - Riofrio, Juan Carlos (Strathmore Law Journal, 2023)
This article presents a comprehensive overview and analysis of Tom Angier’s latest book, “Natural Law Theory”, published in 2021 by Cambridge University Press, and also compares its main conclusions with another study that analyses how natural law scholars have argued over the last century. To achieve this goal, the article initially outlines the core ideas of Angier’s book, which seeks to elucidate and assess the most significant theories of natural law throughout history, with an emphasis on the traditional approach rooted in Aristotle and the Stoics. Angier introduces the innovative “via negativa” method for identifying natural law principles within this framework. Following the exposition of the book’s content, the article draws parallels between Angier’s conclusions and the findings of another research project about the “Natural Law Formula” (or methods) currently used by natural law experts in legal literature. Both Angier and this research observe that contemporary authors face challenges in grounding the principles of natural law in the physical and spiritual human nature. Lastly, the article evaluates the “via positiva” and “via negativa” methodologies, highlighting their potential contradictions and concordances, while suggesting avenues for further refining Angier’s arguments.